2021
DOI: 10.2196/26376
|View full text |Cite
|
Sign up to set email alerts
|

App-Tailoring Requirements to Increase Stress Management Competencies Within Families: Cross-sectional Survey Study

Abstract: Background Families experiencing high levels of psychological distress are considered a particularly vulnerable population for adverse effects on mental and physical health. Moreover, highly stressed individuals engage less in mental health promoting activities and show low stress management competencies. App-based stress interventions seem promising for the treatment and prevention of stress outcomes and might be a low-threshold solution. Objective The… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 79 publications
0
7
0
Order By: Relevance
“…Most of the 22 research articles mentioned the types of healthy lifestyle behavior that may be affected by personality traits and goal achievement. They include exercising, participating in sports, eating a healthy diet, participating in physical activity using electronic devices [ 19 , 20 ], participating in leisure-time physical activity that is “planned, structured, repeated and with maintenance” [ 21 ], controlling one’s weight, managing one’s nutrition [ 22 ], engaging in social activities, and having intentions and beliefs about physical activity [ 23 ]. The literature indicated that people who engage in these HLBs tend to have better physical, mental, emotional, and cognitive health [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of the 22 research articles mentioned the types of healthy lifestyle behavior that may be affected by personality traits and goal achievement. They include exercising, participating in sports, eating a healthy diet, participating in physical activity using electronic devices [ 19 , 20 ], participating in leisure-time physical activity that is “planned, structured, repeated and with maintenance” [ 21 ], controlling one’s weight, managing one’s nutrition [ 22 ], engaging in social activities, and having intentions and beliefs about physical activity [ 23 ]. The literature indicated that people who engage in these HLBs tend to have better physical, mental, emotional, and cognitive health [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, research on M-health indicated that electronic devices, such as a Fitbit, were considered to be effective in facilitating goal setting and achievements. This is because the planning, learning [ 19 ], rewarding, comparing, and sharing functions in electronic devices can trigger individuals’ motivation to achieve their desired goals [ 30 , 48 ]; it is also noteworthy that electronic devices can support personalized goals based on individual personality traits.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One possible explanation for the limited effectiveness of our intervention, in addition to the high dropout rate, is the insufficient incorporation of health behavior change strategies. While our biofeedback app included both active and passive behavior change techniques and promoted stress management skills, some of the content proposed by Bischoff et al [ 112 ] was not implemented. Specifically, we applied individualization of app content, fulfilling common weekly goals and tasks, increasing knowledge about a healthy lifestyle, reminders for objectives, and controlling and checking progress but did not include many suggestions for activities with diaries for documentation and development of strategies or informational or instructional videos.…”
Section: Discussionmentioning
confidence: 99%
“…Digital Interventions can be a low-threshold opportunity for health promotion and are a promising possibility to achieve prevention goals [ 69 , 70 ], even though eHealth literacy is sometimes missing [ 65 ]. The free allocation of time and flexibility of availability were evaluated on a positive note.…”
Section: Introductionmentioning
confidence: 99%